ER stress-induced ITPR1/ANO1 signaling drives trigeminal neuropathic pain through calcium-dependent neuronal hyperexcitability - Lu, Huan-Jun; Shen, Jia-Wen; Ren, Ning-Yi; Hu, Nan; Cen, Jian-Ke; Huang, Meng-Xuan; Song, Si-Yuan; Ma, Ling-Jie; Wu, Xiao-Bo; Li, Xia; Li, Mei-Xian; Wu, Hao; et al. (Springer Verlag, 2026)
Background Endoplasmic reticulum (ER) stress has been implicated in various chronic pain conditions, but its role in trigeminal neuropathic pain (TNP) remains unclear. This study investigates the contribution of ER stress–induced calcium signaling through the inositol trisphosphate receptor 1 (ITPR1) and anoctamin 1 (ANO1) in a mouse model of TNP. Methods A partial infraorbital nerve transection (pIONT) model was used to induce TNP in mice. Mechanical allodynia was assessed using von Frey filaments. ER stress was evaluated via transmission electron microscopy and Western blotting for ER stress markers. Intracellular Ca²⁺ dynamics were measured by Fluo-4 AM-based Ca²⁺ imaging in primary TG neurons. Gene and protein expression were analyzed using qPCR, Western blot, and immunofluorescence. Protein-protein interaction was examined by co-immunoprecipitation. Neuronal excitability and ANO1 currents were recorded by whole-cell patch-clamp. siRNA-mediated knockdown and pharmacological inhibitors were used to interrogate functional contributions. Results pIONT induced pronounced ER stress in TG neurons, evidenced by swollen ER cisternae and upregulated ER stress sensors. Pharmacological alleviation of ER stress in the TG with the chemical chaperone 4-phenylbutyric acid effectively reduced pIONT-induced pain hypersensitivity. Mechanistically, ER stress upregulated the expression of inositol trisphosphate receptor 1 (ITPR1) via the transcription factor RUNX2, and knockdown of RUNX2 attenuated pIONT-induced mechanical allodynia. Moreover, ITPR1 mediates enhanced ER Ca²⁺ release, ERK activation, and the expression of inflammatory mediators, as well as neuronal hyperexcitability in the TG following pIONT. Notably, ITPR1 functionally couples with anoctamin 1 (ANO1), a calcium-activated chloride channel, in TG neurons. An ITPR1 agonist induced ANO1 currents and mechanical allodynia, which were reduced by an ANO1 inhibitor. Finally, knockdown or inhibition of ANO1 reduced neuronal hypersensitivity and TNP pathogenesis. Conclusions ER stress drives TNP through a RUNX2–ITPR1–ANO1 signaling axis: ER stress upregulates RUNX2, which transcriptionally enhances ITPR1 expression, leading to aberrant ER Ca²⁺ release, ERK activation, neuroinflammation, and ANO1-dependent neuronal hyperexcitability. Targeting this pathway may provide a novel therapeutic strategy for TNP.